Analisis Pengendalian Kualitas Produk dengan Metode Statistical Processing Control pada Usaha Bakpia Wirda - Santosa, Rizki Fitra; Irianto, Heru; Khomah, Isti (Program Studi Magister Agribisnis, Universitas Sebelas Maret, 2022)
This study aims to identify the types of product defects, production process control limits, leading problems, factors causing the main issues in the production process, and corrective actions on the main problems in Bakpia Wirda's production. The primary research method is quantitative and qualitative descriptive. The research location is Bakpia Wirda, a bakpia business located in Tasikmadu Sub-district, Karanganyar Regency. The data used in this research are primary and secondary. Data analysis used the statistical processing control method with analytical tools in the form of (1) examination sheet or checksheet, (2) P-chart control diagram, (3) Pareto diagram, and (4) cause and effect diagram. The data taken is bakpia production data for September-October 2021. The results showed that the types of defective bakpia found during the production process were charred bakpia, torn skin bakpia, deformed bakpia, and too hard bakpia. There is one point outside the control limit, namely the point on the 3rd day, outside the upper control limit (UCL). The types of product defects of burnt bakpia and torn skin bakpia are the most dominant problems because they contribute 79.84% of the total product defects. Proposed improvements to the burnt bakpia defect are installing a timer during the roasting process, routine maintenance on the internal components of the stove, and adding a layer of the metal plate under the pan. Meanwhile, the proposed improvement for the torn skin bakpia defect is to increase the number of production workers, expand the production site, and add ventilation holes.